On the Columbia Journal of Gender and Law’s Future Role - Weinstein, Jack B. (Columbia Journal of Gender and Law, 2000)
Providing gender equity and equality in organizations is an important route to major improvements in status and opportunity. In the last ten years, statutory reforms, caselaw, and private changes in attitude have reduced many institutional inequalities-with far more to be done. We need to take a broader view of “gender problems.” Implicated in such a view will be the more intractable sociological problems of individuals in one-on-one relationships or community situations, of single parenthood and of child rearing in nontraditional and traditional families, of the continuing intergenerational effects of poverty, poor education and cruel childhoods, and of heritage-based views of man-woman characteristics and affinities, particularly in terms of real equality of opportunity. That so many are in prison, for example, is a critical aspect of gender issues for the future.